Oligo-Carrageenan Kappa Increases Expression of Genes Encoding Proteins Involved in Photosynthesis, C, N, and S Assimilation, and Growth in Arabidopsis Thaliana - Moenne-Munoz, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
To analyze the effect of oligo-carrageenan (OC) kappa in the stimulation of growth in Arabidopsis thaliana, plants were sprayed on leaves with an aqueous solution of OC kappa at 1 mg mL−1, 5 times every 2 days and cultivated for 5 or 15 additional days. Plants treated with OC kappa showed an increase in rosette diameter, fresh and dry weight, and primary root length. Plants treated with OC kappa once and cultivated for 0 to 24 h after treatment were subjected to transcriptomic analyses to identify differentially expressed genes, mainly at 12 h after treatment. Transcripts encoding proteins involved in growth and development and photosynthesis were upregulated as well as enzymes involved in primary metabolism. In addition, plants treated with OC kappa once and cultivated for 0 to 96 h showed increased levels of transcripts encoding enzymes involved in C, N, and S assimilation at 6 and 12 h after treatment that remain increased until 96 h. Therefore, OC kappa increased the expression of genes encoding proteins involved in photosynthesis, C, N, and S assimilation, and growth in A. thaliana. © 2023 by the authors.